“O estranho mundo de Zé do Caixão” por R. F. Lucchetti: diálogos multimídia e hibridismo no terror brasileiro - Silva, José Aguiar Oliveira da (2019)
Between 1968 and 1969 Mojica and Lucchetti formed a creative partnership that resulted in a multimedia dialog without precedent until then in this country. The screenwriter wrote under the title of "The Strange World of Coffin Joe" three different cultural products: a film, a television serial and a series of comic books. Through the reflection of the dialog between the languages and audiovisual technology with the visual narrative of comic books, you can trace that way if you have changed the original design of Coffin Joe from the moment in which his new scriptwriter brought him a new approach. Technical analysis of the convergence of media that allowed the character to massify, as well as the speech and historical context and social development of those works written by Lucchetti, sets out a vision of how technological development interacts with actors and social resources within cultural industries. The objective of this dissertation is study how the version of Coffin Joe made by Rubens Francisco Lucchetti has contributed to his maintenance with the audience of the genre of terror. Experience that transcended this niche and transformed the character into an icon also in the popular imagination. A controversial and contradict cultural product who found his greatest multimedia reverberation precisely in the conservative and repressive period of military dictatorship in Brazil.